Citizens’ Support for Local Law Enforcement Anti-Counterfeiting Activities - Kennedy, Jay P. (American journal of criminal justice, 2019)
Product counterfeiting is a global crime that can have substantial effects within local communities, particularly with regard to its impact on citizens. Undertaking anti-counterfeiting activities at the local level requires law enforcement agencies to direct resources toward a non-traditional crime problem. Yet, it is unclear whether citizens would be willing to support increasing the financial resources given to local law enforcement to support anti-counterfeiting activities. Our study of Michigan citizens found that most would support such increases, however, support declined when respondents were asked to consider financial and non-financial costs. Our findings suggest that the strongest support for increasing local anti-counterfeiting resources comes from citizens who are willing to support such increases through paying higher taxes, and victims of product counterfeiting. However, policies aimed at increasing resources are not likely to gain wide acceptance unless it can be shown that existing law enforcement missions will be preserved, and resources will not be shifted away from traditional law enforcement functions.